CCL2-dependent infiltrating macrophages promote angiogenesis in progressive liver fibrosis. Issue 12 (21st February 2014) - Ehling, Josef; Bartneck, Matthias; Wei, Xiao; Gremse, Felix; Fech, Viktor; Möckel, Diana; Baeck, Christer; Hittatiya, Kanishka; Eulberg, Dirk; Luedde, Tom; Kiessling, Fabian; Trautwein, Christian; et al.
Abstract : Objectives: In chronic liver injury, angiogenesis, the formation of new blood vessels from pre-existing ones, may contribute to progressive hepatic fibrosis and to development of hepatocellular carcinoma. Although hypoxia-induced expression of vascular endothelial growth factor (VEGF) occurs in advanced fibrosis, we hypothesised that inflammation may endorse hepatic angiogenesis already at early stages of fibrosis. Design: Angiogenesis in livers of c57BL/6 mice upon carbon tetrachloride- or bile duct ligation-induced chronic hepatic injury was non-invasively monitored using in vivo contrast-enhanced micro computed tomography (µCT) and ex vivo anatomical µCT after hepatic Microfil perfusion. Functional contributions of monocyte-derived macrophage subsets for angiogenesis were explored by pharmacological inhibition of CCL2 using the Spiegelmer mNOX-E36. Results: Contrast-enhanced in vivo µCT imaging allowed non-invasive monitoring of the close correlation of angiogenesis, reflected by functional hepatic blood vessel expansion, with experimental fibrosis progression. On a cellular level, inflammatory monocyte-derived macrophages massively accumulated in injured livers, colocalised with newly formed vessels in portal tracts and exhibited pro-angiogenic gene profiles including upregulated VEGF and MMP9. Functional in vivo and anatomical ex vivo µCT analyses demonstrated that inhibition of monocyte infiltration by targeting the chemokine CCL2 prevented fibrosis-associated angiogenesis, but not fibrosis progression. Monocyte-derived macrophages primarily fostered sprouting angiogenesis within the portal vein tract. Portal vein diameter as a measure of portal hypertension depended on fibrosis, but not on angiogenesis. Conclusions: Inflammation-associated angiogenesis is promoted by CCL2-dependent monocytes during fibrosis progression. Innovative in vivo µCT methodology can accurately monitor angiogenesis and antiangiogenic therapy effects in experimental liver fibrosis.